2005
DOI: 10.1158/0008-5472.can-05-1622
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Functional Significance of Thromboxane Synthase Gene Overexpression in Invasive Bladder Cancer

Abstract: Thromboxane synthase (TXAS) is one of the enzymes downstream from cyclooxygenase-2 and catalyzes the synthesis of thromboxane A 2 (TXA 2 ). TXAS was among the genes we identified based on its overexpression in invasive bladder tumors. TXAS is overexpressed in common forms of bladder tumors: 69 of 97 (71.1%) transitional cell carcinoma (TCC), 38 of 53 (71.6%) squamous cell carcinoma, and 5 of 11 (45.5%) adenocarcinoma relative to nontumor tissue. Overall, 112 of 161 (69.5%) invasive tumors exhibited elevated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 45 publications
6
64
0
1
Order By: Relevance
“…The data are representative of seven cases that showed the same pattern of expression. Increased expression of TXAS protein with tumor grade is consistent with that observed with mRNA analyses (Moussa et al, 2005).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The data are representative of seven cases that showed the same pattern of expression. Increased expression of TXAS protein with tumor grade is consistent with that observed with mRNA analyses (Moussa et al, 2005).…”
Section: Resultssupporting
confidence: 85%
“…During molecular profiling of bladder cancer, we found that TXAS is overexpressed in both squamous cell carcinoma and transitional cell carcinoma (TCC) of the bladder (Moussa et al, 2005). Significantly, increased TXAS expression in patients with bladder cancer is negatively correlated with survival (Moussa et al, 2005). TXAS-specific inhibitors have been shown to suppress growth and reduce the migration and invasion of bladder cancer cells (Moussa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of COX-2 expression by a TP agonist would naturally lead to increased PGE 2 and TXB 2 synthesis although we are not sure if the coupling enzymes, PGE synthase and thromboxane synthase, are also induced. However, both microsomal PGE synthase and thromboxane synthase are known to over-express in tumors [29,30], whereas the key PG catabolic enzyme, 15-hydroxyprostaglandin dehydrogenase, is demonstrated to underexpress in tumors [31]. In fact, the expressions of COX-2 and 15-hydroxyprostaglandin dehydrogenase were shown to be regulated reciprocally [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane synthesis has been reported to be elevated in bladder cancers and inhibition of the synthesis or action of these prostanoid mediators can decrease rates of cell proliferation and migration [122]. In the late 1990s it was demonstrated that two isoforms of the thromboxane receptor (TP-α and TP-β), alternatively spliced at the C-terminus, have distinct agonist-induced internalization properties and abilities to bind β-arrestins [80], with only the TP-β isoform able to internalize in a ligand-dependent manner.…”
Section: Alternative Splicing Of Gpcrs In Cancermentioning
confidence: 99%